(untitled) (Perner’s Contacts, 2023)
The rapid advancement of technology in the field of unmanned aerial vehicles (UAVs) has created new possibilities for their application in numerous fields. For every unmanned aerial system it is essential to contain a ground control station (GCS), which must comply with mission-specific requirements. This paper presents the results of our research on optimizing the hardware and software components of radio communication for an UAV prototype with hybrid propulsion and integrating them into one comprehensive control station, enabling long-range operation and universal applicability to other unmanned aircraft. Our approach includes a unique solution to separate flight control from propulsion unit monitoring due to the experimental nature of the propulsion system. Flight safety was also enhanced by equipping the GCS with a system that provides information about nearby air traffic and secures the operational area against unauthorized UAV flights. Our system is capable of detecting intruders and determining their location based on intercepting UAV radio signals. Additionally, we conducted research on radio jamming as a means of interrupting the flight of a UAV that is violating a restricted airspace. Overall, our research provides insights and recommendations for the development of effective and user-friendly GCSs for UAV systems, addressing the critical need for safe and secure UAV operations.